Effect of rolling process on deformation structure and mechanical properties of CoCrFeNiMo0.35 high entropy alloy - Xiuli Ma; Baolin Wei; Xiaoning Feng; Peng Peng; Yuanli Xu; Xudong Zhang; Zhikun Ma (Journal of Materials Research and Technology)
In this work, CoCrFeNiMo0.35 high entropy alloy was hot-rolled at 900 °C by varying different reductions (10%, 20%, 30%, 40%, 50%) and the impact of hot rolling on the structure and mechanical properties of this alloy has been investigated. It is found that the phase composition of CoCrFeNiMo0.35 high entropy alloy after hot rolling has not been changed, and it still consists of FCC phase and σ phase (Cr and Mo-rich phase), which is the same as the as-cast state alloy. Besides, the grain size becomes finer after hot rolling and is stretched to a flat shape in the rolling direction, and the grain orientation gradually changes from <001> and <101> direction to <101> direction with the increase of reduction. At the same time, as the increase of rolling reduction, the volume fraction of σ phase increases, and the yield strength (∼817.8 MPa), tensile strength (∼891.7 MPa) and hardness of the alloy are improved. The comprehensive influence of fine grain strengthening, second phase strengthening and dislocation strengthening is the main reason for this result. Besides, the fracture mode of the tensile sample changes from mixed tough-brittle fracture to brittle fracture. The research results can be used as a reference for hot rolling strengthening of CoCrFeNiMo0.35 high entropy alloy.